A systematic review of Neotropical Caladomyia Säwedal (Diptera: Chironomidae) - Trivinho-Strixino, Susana (Zootaxa, 2012)
Eleven new species of the genus Caladomyia Säwedal, 1981, from lotic and lentic systems of the state of São Paulo are described and figured: Caladomyia angelae sp. n., Caladomyia carolae sp. n., Caladomyia canine sp. n., Caladomyia jaragua sp. n., Caladomyia yara sp. n., Caladomyia capaopreto sp. n., Caladomyia curumim sp. n., Caladomyia bruneola sp. n., Caladomyia comunis sp. n., Caladomyia carolensis sp. n., Caladomyia kapilei sp. n. Additionally the male of C. humboldti Säwedal is redescribed and its immatures and the female are described. Keys to males, pupae and larvae of known species of the genus Caladomyia are provided.